Data processing method and data storage system - Herodotou, Herodotos (My University, 2024)
The application provides a data processing method and a data storage system. The method comprises the steps that a data storage system trains a first streaming model according to a plurality of first access data characteristics corresponding to a first file in an i-1 access request and first access attribute parameters of the first file, then, a plurality of second access data characteristics corresponding to the first file in the i-1 access request are input into the first streaming model, second access attribute parameters of the first file in the i+1 access request are obtained, and then, the first file can be prefetched or migrated according to the second access attribute parameters. Therefore, the method carries out online training on the first streaming model by using a plurality of first access data features, so that consumed storage resources and computational resources are relatively small, the first streaming model can adapt to the continuously-changing file access mode, and the service performance of the data storage system can be effectively improved.
一种数据处理方法及数据存储系统
Keywords: G06F3/0685 - Hybrid storage combining heterogeneous device types, e.g. hierarchical storage, hybrid arrays; Hybrid storage; Data prefetching; G06F12/0862 Addressing of a memory level in which the access to the desired data or data block requires associative addressing means, e.g. caches with prefetch; G06F3/06 Digital input from, or digital output to, record carriers, e.g. RAID, emulated record carriers or networked record carriers